PEMANFAATAN METODE ANALYTICAL HIERARCHY (AHP) DALAM SISTEM PENDUKUNG KEPUTUSAN PENENTUAN BONUS AKHIR TAHUN - Cholifah, Wahyu Nur; Pujiastuti, Pujiastuti; Pauziah, Ulfa (Sekolah Tinggi Manajemen Informatika dan Komputer Jayakarta, 2024)
Determining the year-end bonus is a strategic decision for PT. Dankos Farma in motivating employees and achieving company goals. In this context, the Analytical Hierarchy Process (AHP) method has been implemented as part of the company's decision support system. This study evaluates the use of AHP by PT. Dankos Farma is in the process of determining year-end bonuses. Through AHP, relevant criteria such as individual performance, contribution to the team, and achievement of company targets can be analyzed systematically. The relative weight of each criterion is determined based on company priorities. Alternatives for awarding bonuses are evaluated taking these factors into account. By using AHP, PT. Dankos Farma can make more objective and measurable bonus decisions, increasing transparency and accountability in the process. Additionally, AHP allows companies to adjust bonus policies quickly to changes in corporate strategy or market conditions. In conclusion, the use of AHP by PT. Dankos Farma's decision support system for determining year-end bonuses has helped increase efficiency and effectiveness in decision making related to employee incentives.